Anticipated advantages and disadvantages of a move to 100% single‐room hospital in Australia: A case study. (21st April 2019) - Cusack, Lynette; Wiechula, Rick; Schultz, Tim; Dollard, Joanne; Maben, Jill
Abstract: Objectives: There is an international policy trend for building government hospitals with greater proportions of single‐occupancy rooms. The study aim was to identify advantages and disadvantages for patients and nursing staff of a pending move to 100% single‐room hospital, in anticipation of the challenges for nurse managers of a different ward environment. This paper presents these findings, summarizing potential advantages and disadvantages as well as comparison with findings from similar studies in England. Methods: Mixed method case study design was undertaken in four wards of a large hospital with multi‐bed rooms. Three components of a larger study are reported here: nurse surveys and interviews, patient interviews of their experiences of the current multi‐bedroom environment and expectations of new single‐room environment. Integration was achieved via data transformation where results of the nursing staff survey and interviews and patient interviews were coded as narrative allowing for quantitative and qualitative data to be merged. Results: Four constructs were derived: physical environment; patient safety and comfort; staff safety; and importance of interaction. Conclusion: There are important factors that inform nurse managers when considering a move to an all single‐room design. These factors are important for nurses' and patients' well‐being. Implications for nursing management: This study identified for nurse managers key factors that should be considerd when contributing to the design of a 100% single‐room hospital. Nurses' voices are critically important to inform the design for a safe and efficient ward environment.